Alfaxalone Causes Reduction of Glycinergic IPSCs, but Not Glutamatergic EPSCs, and Activates a Depolarizing Current in Rat Hypoglossal Motor Neurons - Lau, Cora; Thakre, Prajwal P.; Bellingham, Mark C. (Frontiers in Cellular Neuroscience, 2019)
We investigated effects of the neuroactive steroid anesthetic alfaxalone on intrinsic excitability, and on inhibitory and excitatory synaptic transmission to hypoglossal motor neurons (HMNs). Whole cell recordings were made from HMNs in brainstem slices from 7 to 14-day-old Wistar rats. Spontaneous, miniature, and evoked inhibitory post-synaptic currents (IPSCs), and spontaneous and evoked excitatory PSCs (EPSCs) were recorded at –60 mV. Alfaxalone did not alter spontaneous glycinergic IPSC peak amplitude, rise-time or half-width up to 10 μM, but reduced IPSC frequency from 3 μM. Evoked IPSC amplitude was reduced from 30 nM. Evoked IPSC rise-time was prolonged and evoked IPSC decay time was increased only by 10 μM alfaxalone. Alfaxalone also decreased evoked IPSC paired pulse ratio (PPR). Spontaneous glutamatergic EPSC amplitude and frequency were not altered by alfaxalone, and evoked EPSC amplitude and PPR was also unchanged. Alfaxalone did not alter HMN repetitive firing or action potential amplitude. Baseline holding current at −60 mV with a CsCl-based pipette solution was increased in an inward direction; this effect was not seen when tetrodotoxin (TTX) was present. These results suggest that alfaxalone modulates glycine receptors (GlyRs), causing a delayed and prolonged channel opening, as well as causing presynaptic reduction of glycine release, and activates a membrane current, which remains to be identified. Alfaxalone selectively reduces glycinergic inhibitory transmission to rat HMNs via a combination of pre- and post-synaptic mechanisms. The net effect of these responses to alfaxalone is to increase HMN excitability and may therefore underlie neuro-motor excitation during neurosteroid anesthesia.